A simple clinical score for estimating the long-term risk of fracture in post-menopausal women. - van Staa, T; Geusens, P; Kanis, J; Leufkens, H; Gehlbach, S; Cooper, C (2006)
BACKGROUND: Simple tools are needed to identify patients at high risk of fracture. AIM: To develop a simple clinical tool for assessing 5-year risk of fracture. DESIGN: Cohort study. METHODS: The study population consisted of all women aged 50+ included in the THIN Research Database (containing computerized medical records of UK general practices). Using Cox proportional hazards models, a risk score was initially estimated from age, body mass index, and clinical risk factors. The 5-year risk of fracture (survival function) was estimated for each score. RESULTS: The study population included 366 104 women aged > or = 50 years (mean follow-up 5.8 years). Of these, 6453 suffered a hip fracture. Several characteristics independently contributed to the fracture risk score (age, body mass index, fracture and fall history, previous diagnoses and use of medication). The 5-year risks for hip fracture for patients with total scores of 10, 30 and 50 were 0.3% (95%CI 0.3-0.4%), 2.2% (95%CI 2.1-2.2%), and 13.1% (95%CI 12.5-13.7%), respectively. A woman aged 65 years with low BMI and a history of both fracture and falling would have a hip fracture risk score of 37, with a corresponding 5-year risk for a hip fracture of 4.1% (4.0-4.2%). The risk score was validated and tested in another population (from GPRD), with a good concurrence between predicted and observed risks of fracture. DISCUSSION: This risk score predicts the long-term risk of fracture, and could be used for targeting patients for further investigation, such as bone densitometry.